Application of Mobile GIS and the Flora Incognita App for Documenting Vegetation Along the Green Ecological Trail in the Barlinek Landscape Park - Pawlik, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article examines the use of mobile Geographic Information Systems (GIS), particularly the Flora Incognita application, for documenting vegetation along the green ecological trail in the Barlinek Landscape Park. The study evaluates the usability of the application, the accuracy of plant identification, and its potential to generate high-quality georeferenced data. The results indicate that Flora Incognita is an efficient and cost-effective tool for rapid floristic surveys, achieving high identification accuracy which, when complemented by expert verification, can significantly enhance monitoring efforts.
Keywords: mobile GIS; Barlinek Landscape Park; floristic documentation; biodiversity; citizen science